2021
DOI: 10.1007/s00127-021-02147-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of medical service fee revision on reducing irrational psychotropic polypharmacy in Japan: an interrupted time-series analysis

Abstract: Purpose According to the revised Japanese medical service fees aimed at reducing irrational psychotropic polypharmacy, medical service fees are reduced if the number of simultaneously prescribed psychotropic drugs exceeds the standard. This study primarily aims to examine the effect of the 2018 revision. Methods Using a large Japanese administrative claims database, we retrospectively identified five groups (April 2013–September 2018) prescribed at least o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…After the release of the expert consensus, both the prevalence of polypharmacy and PIM use decreased, especially the prevalence of PIM use. Regarding measures to reduce polypharmacy, studies have shown that unreasonable psychotropic drug polypharmacy in Japan can be reduced by revising the fee of medical services ( Hirano and Ii, 2019 ; Okada and Akazawa, 2022 ). In addition, there was a study on the application of electronic medicine reconciliation, which reduced the PIM use of elderly inpatients in tertiary hospitals after discharge and transfer to the community in Canada ( Welk et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…After the release of the expert consensus, both the prevalence of polypharmacy and PIM use decreased, especially the prevalence of PIM use. Regarding measures to reduce polypharmacy, studies have shown that unreasonable psychotropic drug polypharmacy in Japan can be reduced by revising the fee of medical services ( Hirano and Ii, 2019 ; Okada and Akazawa, 2022 ). In addition, there was a study on the application of electronic medicine reconciliation, which reduced the PIM use of elderly inpatients in tertiary hospitals after discharge and transfer to the community in Canada ( Welk et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that polypharmacy of psychotropic drugs causes negative drug effects, such as fall and impaired cognitive function [8][9][10]. In response to this issue, medical service fee revisions on multi-psychotropic drug prescriptions were implemented from 2012 to 2018 in Japan [11][12][13]. In Japan, "the Healthcare bill check and payment organization" checks claims data and pays medical costs directly to the medical facilities instead of the health insurers in the health insurance system.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, fees for the prescription and medication are not reduced when psychotropic medications are prescribed temporarily or when antipsychotics or antidepressants are unavoidably prescribed by a doctor with sufficient training in psychiatric clinical practice. As a result, the proportion of multi-psychotropic drug prescriptions decreased over the years in Japan [12,13]. Identification of patient traits or geographic areas linked to the multi-psychotropic drug prescriptions is crucial for furthering the improvement of multi-drug prescriptions.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that the 2018 amendment effectively reduced polypharmacy. However, the data for that study were drawn from a claims database maintained by a private company that does not include data from patients aged 75 years and above [ 18 ]. Therefore, information about recent long-term trends regarding nationwide polypharmacy in Japan that includes adults aged 75 years and above is lacking.…”
Section: Introductionmentioning
confidence: 99%